Montecarlo Application on Nucleon Dynamics in Calculating Fission Yield at 14 MeV Neutron Energy - rizal kurniadi (Indonesian Journal of Physics, 2023)
Nuclear data is a completeness that must be present in every activity related to nuclear technology. So high is the role of nuclear data, it is necessary to have very complete nuclear data. The need for nuclear data is not in line with the resulting experimental products. The amount of experimental data needs to be completed. This is because the operational costs for these experiments are costly. Thus, theoretical modeling calculations are inevitably the right choice to replace experimental results. Many theoretical models have been developed to obtain satisfactory results. They were starting from microscopic models to macroscopic models. A common obstacle is that microscopic models must be simplified and efficient to produce massive nuclear data. Meanwhile, the constraints on the macroscopic model could be more accurate. This paper will present a calculation that tries to produce accurate but uncomplicated and economical data. This technique uses the basic principles of random numbers and classical nucleon dynamics in the nucleus. At the end of the paper, the results of calculations are presented, which are very accurate and, at the same time, show the dynamics of the nucleons that occur.